Cerebral concussion in sport: An overview - Echemendia, R. J. (Journal of Clinical Sport Psychology, 2012)
Sports-related concussions are ubiquitous in contact and collision sports at all levels of play and across a broad age range. Once thought to be a nuisance injury, it is now recognized that these brain injuries may lead to chronic neurocognitive impairment if not managed properly. This paper provides a broad overview of the research and clinical data that have emerged in this rapidly growing area. Included in the review are discussions of injury definition, pathophysiology, signs and symptoms, epidemiology, potential long-term consequences, assessment, and psychological factors. Issues of prevention and education are discussed in light of further increasing awareness of this injury.